PENGARUH JUS KURLAPA DALAM PENINGKATAN HB PADA REMAJA PUTRI PENDERITA ANEMIA DI DESA KARANGRAHARJA - Ida Widaningsih (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Iron deficiency anemia can have various effects on young women, including lowering the body's resistance so that it can reduce fitness, decrease activity, and learning achievement. The purpose of this research was conducted to know the effect of kurlapa juice (dates and coconut water) in increasing hemoglobin in adolescent patients. Research using a quasi-experimental design without a control group using a one-group pretest-posttest design approach, the sample used was 30 young women with a random sampling technique. Statistical analysis used Paired T-test. The results of the study obtained a p-value of 0.000 which means that there is an influence of kurlapa juice on anemia in young women.